Experiences of physiotherapists regarding a standard set of measurement instruments to improve quality of care for patients with chronic obstructive pulmonary disease: a mixed methods study - Arie C. Verburg; Jessica Zincken; Henri Kiers; Simone A. van Dulmen; Philip J. van der Wees (SpringerOpen, 2022)
Abstract Rationale The quality of physiotherapy care for patients with chronic obstructive pulmonary disease (COPD) can be improved by comparing outcomes of care in practice. Aim To evaluate the experiences of physiotherapists implementing a standard set of measurement instruments to measure outcomes and improve the quality of care for patients with COPD. Methods This sequential explanatory mixed methods study was performed in two parts. In the quantitative part, a survey of 199 physiotherapists was conducted to evaluate their attitudes and knowledge, as well as the influence of contextual factors (i.e., practice policy and support from colleagues), in the implementation of the standard measurement set. In the qualitative part, 11 physiotherapists participated in individual interviews to elucidate their experiences using a thematical framework. Results The survey showed that, on average, 68.4% of the physiotherapists reported having a positive attitude about using the standard set, 85.0% felt they had sufficient knowledge of the measurement instruments, and 84.7% felt supported by practice policy and colleagues. In total, 80.3% of physiotherapists thought the standard set had added value in clinical practice, and 90.3% indicated that the measurement instruments can be valuable for evaluating treatment outcomes. The physiotherapists mentioned several barriers, such as lack of time and the unavailability of the entire standard set of measurement instruments in their practice. Moreover, the physiotherapists indicated that the measurement instruments have added value in providing transparency to policymakers through the anonymized publication of outcomes. Conclusion Physiotherapists support the use of the standard set of measurement instruments to improve the quality of physiotherapy treatment for patients with COPD.